A Pilot Investigation of the Effect of Transport-Related Factors on Care Quality in a Moving Ambulance. Issue Volume 34:Issue s1(2019) (May 2019) - Prytz, Erik; Åkerstedt, Zandra; Lidestam, Björn; Lampi, Maria; Jonson, Carl-Oscar
Abstract : Introduction: Providing patient care in a moving ambulance can be difficult due to various transport-related factors, (e.g., accelerations, lateral forces, and noise). Previous research has primarily focused on cardiopulmonary resuscitation (CPR) performance effects but has neglected to investigate other care interventions. Aim: To test a range of different care interventions during different driving scenarios. Methods: A workshop with ambulance practitioners was held to create a list of care interventions to be tested. Two ambulance practitioners were recruited to drive an ambulance on a closed test-track while performing care interventions on simulation models. Three driving scenarios of differing difficulty were used. Main outcome measures were estimates of workload using the NASA Task Load Index (TLX) and task difficulty. G-forces and video-data were also collected. Results: Estimated workload increased overall as the difficulty of the driving scenario increased, as did task difficulty estimates. However, some care scenarios and interventions were affected less. For example, placing intravenous access increased greatly in difficulty, whereas saturation and blood pressure measurements had more modest increases. TLX scores showed that the primarily estimated physical workload and effort that increased, but also mental and temporal demands for some care scenarios. The more difficult driving scenarios primarily increased the variability of measured G-forces but not necessarily the overall driving speed, indicating that force variability is an important factor to study further. Discussion: The study was intended as an initial pilot test of a wide range of care interventions. It will serve as input to future, larger studies of specific interventions and transport-related factors. Overall, this small pilot indicates that more interventions than only CPR should be studied in moving ambulances to investigate potential performance effects. This is important for traffic, patient, and work safety for ambulance workers and patients.